Estudo da mirmecofauna aplicado na avaliação de áreas de garimpo de diamantes no município de Poxoréu, MT - Rocha, Wilian de Oliveira (2012)
In order to evaluate the extent of environmental degradation promoted by human actions in diverse natural environments, has used living organisms such as ants, by their population characteristics strongly related to the environment. Thus, this study aimed to evaluate qualitatively and quantitatively the species of ants (Hymenoptera) occurring in an area degraded by mining diamonds to set the bioindicators of this degradation, and thus assess the level of environmental change promoted by the mining of diamonds. The study was conducted at Limeira Farm in Poxoréu, Mato Grosso state, Brazil, which has defined four distinct environments: A1 - area degraded by mining, A2 - adjacent to the mined area with savannah vegetation with traces of human actions recently, A3 - savannah vegetation disturbed 30 years ago and being adjacent to the preserved savannah area, A4 - savannah area preserved. In each environment was installed along a transect, with 11 "pitfall" traps equidistant 15 meters from each other, to collect ants on a 24 hours period. The samples were collected bimonthly between June 2010 and April 2011. The individuals collected were screened and taxonomically identified to genus and species. The analysis of variance, faunal analysis and cluster analysis were performed to indicate the bioindicators and evaluate the influence of degradation. Analysis of variance showed no significant difference between the four environments when considering the number of individuals in each, however, a significant difference between seasons (rainy and dry) for the number of individuals. The faunal analysis allowed to conclude that Camponotus (Myrmaphaenus) sp.1 and Forelius brasiliensis can be considered as bioindicators of environmental degradation by mining of diamonds and human disturbance, and that Camponotus atriceps, Pachycondyla crassinoda and Paraponera clavata may be considered bioindicators of preserved savannah and stable ecologically, this area of study.